Comparison of Steroidogenic Exposure Following the Administration of Repository Corticotropin Injection With a Synthetic ACTH 1‐24 Depot and Methylprednisolone in Healthy Subjects - Wang, Xiaofeng; Pham, Loan; Poola, Nagaraju; Brooks, Leah R.; Due, Bryan (Clinical pharmacology in drug development, 2021)
The pharmacokinetics (PK) and pharmacodynamics (PD) of clinically relevant doses of repository corticotropin injection (Acthar Gel) and synthetic ACTH 1‐24 depot have not been fully characterized. We compared the steroidogenic exposure of repository corticotropin injection and synthetic ACTH 1‐24 depot in healthy adults at therapeutic doses using data from 2 separate phase 1 studies. Subjects were randomly assigned to repository corticotropin injection 40 or 80 IU subcutaneously twice weekly or 80 IU subcutaneously 3 times weekly for 15 days or to daily synthetic ACTH 1‐24 depot doses of 0.5 mg subcutaneously, 0.75 mg subcutaneously, 1 mg subcutaneously, or 1 mg intramuscularly for 5 days. A population PK/PD model was developed to simulate the free cortisol exposure of a clinically relevant dose of synthetic ACTH 1‐24 depot (1 mg subcutaneously twice weekly). Study drug doses were converted to methylprednisolone‐equivalent doses using the steroidogenic exposure of methylprednisolone 16 mg daily as a conversion factor. Doses were also converted to prednisone equivalents using a coefficient of 1.25. These analyses revealed that the steroidogenic exposure of repository corticotropin injection at clinically relevant doses was substantially lower than that for synthetic ACTH 1‐24 depot. The 3 repository corticotropin injection regimens were equivalent to approximately 5, 8, and 16 mg of daily prednisone, respectively. On the basis of simulated free cortisol exposure, synthetic ACTH 1‐24 depot 1 mg subcutaneously twice weekly was comparable to 57 mg of daily prednisone. These results suggest that repository corticotropin injection has pharmacological effects that cannot be considered identical to synthetic ACTH 1‐24 depot.